Toward a new model of human resource management practices: construction and validation of the High Wellbeing and Performance Work System Scale - Parent-Lamarche, Annick; Dextras-Gauthier, Julie; Julien, Anne-Sophie (Frontiers in Psychology, 2023)
The integrated mutual gains model suggests five provisional sets of human resource management (HRM) practices that should benefit both employees and organizations and, as such, be explicitly designed to have a positive impact on well-being, which, in turn, can affect performance. An extensive review of the literature on scales that used a high-performance work system to assess HRM practices, as well as an extraction of items related to the theoretical dimensions of the integrated mutual gains model, were performed. Based on these preliminary steps, an initial scale with the 66 items found most relevant in the literature was developed and assessed regarding its factorial structure, internal consistency, and reliability over a two-week period. Exploratory factorial analysis following test-retest resulted in a 42-item scale for measuring 11 HRM practices. Confirmatory factor analyses resulted in a 36-item instrument for measuring 10 HRM practices and showed adequate validity and reliability. Even though the five provisional sets of practices were not validated, the practices that emerged from them were assembled into alternative sets of practices. These sets of practices reflect HRM activities that are considered conducive to employees’ well-being and, consequently, their job performance. Consequently, the “High Well-Being and Performance Work System Scale” was created. Nonetheless, future research is necessary to evaluate the predictive capacity of this new scale.